RESPON PETANI TERHADAP BUDIDAYA PADI SAWAH DI KECAMATAN SELUMA SELATAN KABUPATEN SELUMA - Rahmat Oktafia; Ahmad Damiri; Linda Harta; Robiyanto (Program Studi Agribisnis Universitas Sumatera Selatan, 2022)
Food in Indonesia is often identified with rice or rice because this type of food is a staple food for Indonesian people. The task meeting of researchers and extension workers of Balitbangtan and extension workers of Bengkulu province carried out demonstration plots for lowland rice cultivation. The purpose of this study was to examine the response of farmers to lowland rice cultivation technology and the factors related to the response of farmers in Padang Merbau Village, Seluma Selatan District, Seluma Regency. This response research was conducted using survey methods and distributing questionnaires. Sampling was carried out by purposive sampling with 35 respondents consisting of 8 cooperative farmers and 28 farmers around the location in the demonstration plot for innovation in rice cultivation technology. The data collected includes the characteristics of farmers and farmers' responses to technological innovations in lowland rice cultivation. The data obtained were analyzed descriptively quantitatively. The results showed that the response of farmers to technological innovations in lowland rice cultivation was included in the high category with an average score of 3.89, the correlation of respondent characteristics with farmer responses was not significantly related with a value > 0.05. Support from all parties is needed to support farmers' responses to lowland rice technology innovations.